PROX1 is a predictor of survival for gliomas WHO grade II - Elsir, Tamador; Qu, M.; Berntsson, S. G.; Orrego, A.; Olofsson, T.; Lindström, M. S.; Nistér, M.; Deimling, Andreas von; Hartmann, Christian; Ribom, D.; Smits, A. (British journal of cancer, 2011)
The clinical course of World Health Organisation grade II gliomas remains variable and their time point of transformation into a more malignant phenotype is unpredictable. Identification of biological markers that can predict prognosis in individual patients is of great clinical value. PROX1 is a transcription factor that has a critical role in the development of various organs. PROX1 has been ascribed both oncogenic and tumour suppressive functions in human cancers. We have recently shown that PROX1 may act as a diagnostic marker for high-grade gliomas. The aim of this study was to address the prognostic value of PROX1 in grade II gliomas.